Research on intrusion detection algorithm in wireless network based on Bayes game model - CHEN Hang1; TAO Jun1 (Tongxin xuebao)
Bayes game theory was used to research parameter adjustment problems in wireless network intrusion detec-tion.Intrusion detection game model was designed,time interval adjust algorithm TSMA-BG and parameter correction algorithm DPMA were also designed according to the perfect equilibrium in game modeling.Simulation results show that intrusion detection systems can effectively use these algorithms to detect intrusion behavior that have been changed.